Travel Package Recommendation System Based on Package Locations and Rating using Collaborative filtering algorithm - Deshmukh, Sonal; Jadhav, Dipali; Sanap, Pragati; Undre, Pratik V; Mahajan, Yogeshwari (International Journal of Computer Sciences and Engineering, 2025)
Over the decades, travel has toughened continuous growth and deepening diversification to become one amongst the quickest growing economic sectors within the world. Among the present move applications, solely one or two facilitate the flexibility to arrange a tour that is entirely supported user preferences, whereas giving an in-depth inspect the specified destination. Therefore, this analysis focuses on integration Semantic technologies and Collaborative filtering into the domain of travel and supply most well-liked user familiarized tour plans with superlative user satisfaction. Collaborative filtering is applied to spot a set of elective purpose of interested that maximize the potential satisfaction, whereas there are some pre-selected necessary points traveler should visit. The key issue that has to be understood is that the preferences or the behavior of one user is also entirely totally different from another. The system has introduced the idea of preferences and behavior based customized tour coming up with and also the approach of exploring desired routes.